Acute treatment of severe migraine: a literature review - Pinheiro, Giulia Rebouças; Nunes, Melyssa Maria Fernandes da Rocha; Azevedo, Marina Pinheiro Uchoa; Filho, Otavio Pereira da Silva; Lousada, Lívio Martins; Coutinho, Isadora Pinheiro; Soares, Ana Clara Mendes; Moura, Lucas Eliel Beserra (Headache Medicine, 2023)
Full abstract in PDF.